A study on awareness of personal accident insurance among policyholder in Pontian City, Johor / Muhammad Saifullah Sulaiman - Sulaiman, Muhammad Saifullah (Faculty of Business and Management, 2015)
Personal Accident Insurance is the protection that provided to road users that result from accident. The protection given by the Personal Accident Insurance will be able to secure a one off monetary payment to the driver and passengers who are suffering a physical harm, permanently disability & death. The study is conducted to survey on the factors that influence to level awareness of Personal Accident Insurance among motor insurance policyholders in Pontian city, Johor. This is because nowadays, many road accidents may result with serious bodily injury and the most unfortunately may result as a death. Therefore, Personal Accident Insurance are important to reduce the impact of financial loss to the policyholders and beneficiaries. This study shows that there are three factors will influence the level of awareness of policyholder towards the personal accident insurance, which are the marketing, level of income and level of knowledge. As a conclusion, the marketing, level of income and level of knowledge have a positive strong correlation in influencing the policyholders to buy the Personal Accident Insurance.